Chronique juridique : jugements récents - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 1986)
Following our last publication of April 1986, the author briefly comments on certain lawsuits published in Jurisprudence-Express in 1985. This summary, intented for the broker or layman, does not aim to give full details of the lawsuits examined; rather it focuses on the main facts and the sentence rendered. This article may prove useful in helping readers understand the sentence and its ramifications.